Workshop Ilmu Fisika dan Aplikasinya untuk Guru Sekolah Dasar dan Menegah di Desa Oelnasi Kupang Tengah - Albert Zicko Johannes; Jonshon Tarigan; Minsyahril Bukit; Zakarias S. Ngara; Hery L. Sianturi (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
In this paper, we demonstrate physical science training and its application for primary and secondary school teachers in Oelnasi Village, Kupang Regency, East Nusa Tenggara Province. Oelnasi Village is a new potential area in the development of science and technology (IPTEK) due to the availability of a national astronomical observation center in this area. The development of science and technology requires the development and improvement of knowledge related to natural phenomena. To realize this, we, Physics Lecturers at the Physics Study Program of the Faculty of Science and Technology, University of Nusa Cendana, carry out an activity to increase knowledge for elementary and junior high school teachers in Oelnasi village and around through physics training and its application. in community service activities. This activity is carried out in the form of a workshop session where the speaker provides the latest physics and development materials followed by a question and answer session. This activity can open insights and increase knowledge in the field of physics and its application for teachers.